The Saving Retention Coefficient After the Advent of Euro - Panayotis Kapopoulos; John Paleologos (Kredit und Kapital, 2004)
Der Sparkoeffizient nach der Einführung des Euro Die Einführung des Euro stellt einen Meilenstein im Prozess der Integration der europäischen Finanzmärkte dar. Kapitalmobilität ist für die Bewältigung des Verlustes an fiskalpolitischen Instrumenten in der Europäischen Währungsunion hilfreich. Eine hohe Kapitalmobilität im Sinne von Feldstein und Horioka kann die negativen Konsequenzen von Schocks begrenzen, welche die Möglichkeiten einer Volkswirtschaft der Euro-Zone zur Bildung von Ersparnissen beeinträchtigen. Dies bedeutet mit anderen Worten, dass, wenn die Kapitalmobilität hoch ist, die Wachstumsaussichten eines Landes durch seine Möglichkeiten der Ersparnisbildung nicht beeinträchtigt werden. Dieser Beitrag beinhaltet eine empirische Untersuchung des Koeffizienten für die Ersparnisbildung in einer institutionell ausgerichteten Umgebung von fast perfekter Kapitalmobilität und Kapitalmarktintegration, d.h. in Ländern der Euro-Zone. Wir haben auch versucht zu klären, ob die Einführung des Euro und die zuvor vollendete Liberalisierung der Finanz- – – The Saving Retention Coefficient After the Advent of Euro The introduction of the euro marks a milestone in the process of European financial market integration. Capital mobility is helpful to cope with the loss of fiscal adjustment instruments in EMU. High capital mobility in the sense of Feldstein and Horioka can limit the negative consequences of shocks affecting the saving capacity of an economy in the Euro zone. In other words, if capital mobility is high, a country's growth prospect will not be constrained by its ability to save. This paper empirically examines the magnitude of the saving retention coefficient in a setting of an institutionally targeted near-perfect capital mobility and capital market integration, Euro Area countries. We also try to clarify whether the adoption of the euro and the previously completed financial liberalisation has changed the slope of saving-investment association. For this purpose, the Feldstein/ Horioka approach is extended and updated. We find that the savings retention coefficient is relatively low for the whole EMS period but significantly different from zero. Also, the empirical findings support a new puzzle. Domestic saving and investment within EMU is less correlated than they were before the advent of the euro. This result does not support the Frankel's (1992) proposition that the correlation observed between savings and investment is partly due to a non-zero currency premium. However, this result could be considered as preliminary, given the short sample size after the advent of euro. (F32, E22, G15)
Keywords: 330